THE MULTIMODALITY SEMIOTIC ANALYSIS : OPPRESSION OF MENSTRUATING WOMEN IN VIERRATALE'S YOUTUBE MUSIC VIDEO “DATANG BULAN” - Ramadaniar, Putri; Sukmono, Ilham; Reza Akbar, Muhamad; Kuswanti, Ana (Jurnal Sosial Humaniora Sigli, 2024)
In the era of pop culture, women are closely related to oppression in all areas of life by Patriarchal thinking. The menstrual condition experienced by women becomes a weapon of oppression to be able to limit and marginalize women in society. This condition is realized in Vierratale's YouTube music video entitled "Datang Bulan" which was released on June 30, 2023. Through the analytical knife of Kress and Leeuwen's Multimodal Semiotics and Intersectionality Theory, it can uncover the forms of oppression that have been carried out by the music creator. The results of this research analysis show that there has been oppression of menstruating women through the dichotomy of language in using the word woman, the glorification of menstruating women with new myths created and the disproportionality (marginalization) of women to be involved in voicing equality is clearly conveyed in the music video